Deffated microalgae Nannochloropsis sp. as a feed ingredient for Atlantic salmon (Salmon salar). Effect on growth, feed utilisation, digestibility and physical quality of feed - Bjarnason, Fridrik (Nord universitet, 2016)
Masteroppgave i havbruk - Nord universitet, 2016 Sperra for utlån til 2019-09-01